2014
DOI: 10.3857/roj.2014.32.2.84
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac dose reduction with breathing adapted radiotherapy using self respiration monitoring system for left-sided breast cancer

Abstract: PurposeTo quantify the cardiac dose reduction during breathing adapted radiotherapy using Real-time Position Management (RPM) system in the treatment of left-sided breast cancer.Materials and MethodsTwenty-two patients with left-sided breast cancer underwent CT scans during breathing maneuvers including free breathing (FB), deep inspiration breath-hold (DIBH), and end inspiration breath-hold (EIBH). The RPM system was used to monitor respiratory motion, and the in-house self respiration monitoring (SRM) system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 23 publications
4
30
0
Order By: Relevance
“…However, cardiac protection is still a debatable question due to gravityinduced anterior heart displacement toward the irradiated region [13,30,31]. Dosimetric data showed that whole-breast irradiation is superior in prone position over supine position for heartsparing, especially in patients with large breast volumes [18,19,32]. On the other hand, comparative dosimetric data are available, supine deep inspiration breath-hold treatment is better at heartsparing than treatment using a free-breathing prone technique [13,30].…”
Section: Discussionmentioning
confidence: 99%
“…However, cardiac protection is still a debatable question due to gravityinduced anterior heart displacement toward the irradiated region [13,30,31]. Dosimetric data showed that whole-breast irradiation is superior in prone position over supine position for heartsparing, especially in patients with large breast volumes [18,19,32]. On the other hand, comparative dosimetric data are available, supine deep inspiration breath-hold treatment is better at heartsparing than treatment using a free-breathing prone technique [13,30].…”
Section: Discussionmentioning
confidence: 99%
“…Calculated doses to the PTV and organs at risk according to three radiotherapy plans. from RT-associated heart disease was reported to offset the improvement of cancer-specific survival due to adjuvant RT (11,12). A clear quantitative dose-volume dependence for the majority of cardiac toxicities remains to be determined (10).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, however, suggested that the rates of major coronary events increase linearly with the mean heart dose by 7.4% per Gy, with no apparent threshold (13). In addition, it has been established that various clinical parameters may aggravate the risk of radiation-induced heart injury; these include age, diabetes mellitus, smoking, hypertension and the use of cardiotoxic anthracycline-containing chemotherapy (10,12). Re-irradiation for painful spine metastases may be required in patients who achieve no pain relief following initial RT or those who outlive the duration of the first RT response.…”
Section: Discussionmentioning
confidence: 99%
“…Other than optimisation of beams and shielding, the utilisation of breath-hold techniques is another technique to reduce the dose to the heart in the tangential beam path. [38][39][40] The use of physical wedges used on the lateral tangent in conventional planning, is associated with a three-fold increase in scattered dose compared with virtual wedges or hybrid IMRT. 41,42 This is observed in the contralateral breast parameters with the mean, V5 and V1 doses showing a decrease in the hybrid arms.…”
Section: Discussionmentioning
confidence: 99%